Using Podcasts to Improve Listening Skills in Pharmacy Students - Desmiyanti (Universitas Adiwangsa Jambi, 2024)
Language is a system of communication used by a community or group of people. Listening is an important skill in interacting with others in everyday life. This study aims to see how (1) The theoretical perspective of the use of Podcasts on English (2) The use of Podcasts in English courses to improve Listening Skills in Pharmacy Students. This research is a type of qualitative method through literature study. This method referred to as qualitative literature analysis, involves the review and interpretation of descriptive, interpretative, or qualitative analysis of library materials. The results of this study (1)The theoretical perspective of the use of Podcasts on English, namely based on the research that has been done, students feel the positive impact of using Podcasts in teaching English. Students have a fairly good perception of the use podcasts in improving English listening skills. (2)The use of Podcasts in improving listening skills in pharmacy students that is podcasts are able to increase understanding and absorption of information. Pharmacy students can improve listening skills in the health sector. How to improve listening skills is one of them by listening to podcasts. keywords: Podcasts, Listening Skills, Pharmacy Students